Determining the relationship between serum acute phase reactants and cervical premalignant lesions - Sabır, Yeliz Acar; Çift, Tayfur; Karaşin, Süleyman Serkan (São Paulo Medical Journal, 2023)
BACKGROUND: Acute phase reactants play a role in the progression and prognosis of many malignant and premalignant tumors. This study investigated the diagnostic value of certain reactants as markers for cervical premalignant lesions. OBJECTIVES: Despite advanced screening and vaccination programs, cervical cancer remains a serious health problem worldwide. We aimed to determine the possible relationship between premalignant cervical disease and serum acute phase reactant levels. DESIGN AND SETTING: This study included 124 volunteers who underwent cervical cancer screening. We divided the patients into three groups according to cervical cytology and histopathological findings as follows: no cervical lesion, low-grade neoplasia, or high-grade neoplasia. METHODS: We included women aged 25–65 years with benign smear or colposcopy results, low- and high-grade squamous intraepithelial lesions. The benign group was based only on cytology findings, whereas the other groups were based on histopathology findings. Demographic data and serum albumin, fibrinogen, ferritin, and procalcitonin levels were evaluated in the three groups. RESULTS: We found significant differences among the three groups in terms of age, albumin level, albumin/ fibrinogen ratio, and procalcitonin level. The regression analysis revealed lower serum albumin levels in the low- and high-grade squamous intraepithelial lesion groups compared with the benign group. CONCLUSION: This is the first study to evaluate the importance of serum inflammatory markers in cervical intraepithelial lesions. Our results indicate that serum albumin level, albumin/fibrinogen ratio, procalcitonin level, and neutrophil values differ among cervical intraepithelial lesions.